Optimized atomic layer deposition of homogeneous, conductive Al2O3 coatings for high-nickel NCM containing ready-to-use electrodes. Issue 11 (12th March 2021) - Negi, Rajendra S.; Culver, Sean P.; Wiche, Miguel; Ahmed, Shamail; Volz, Kerstin; Elm, Matthias T.
Abstract : The conductive atomic force microscopy study reveals that ultrathin, ALD-derived Al2 O3 coatings preserve the electronic surface conductivity of ready-to-use Ni-rich NCM cathodes during cycling, which is beneficial for their long term cycling stability. Abstract : Atomic layer deposition (ALD) derived ultrathin conformal Al2 O3 coating has been identified as an effective strategy for enhancing the electrochemical performance of Ni-rich LiNi x Co y Mn z O2 (NCM; 0 ≤ x, y, z < 1) based cathode active materials (CAM) in Li-ion batteries. However, there is still a need to better understand the beneficial effect of ALD derived surface coatings on the performance of NCM based composite cathodes. In this work, we applied and optimized a low-temperature ALD derived Al2 O3 coating on a series of Ni-rich NCM-based (NCM622, NCM71.51.5 and NCM811) ready-to-use composite cathodes and investigated the effect of coating on the surface conductivity of the electrode as well as its electrochemical performance. A highly uniform and conformal coating was successfully achieved on all three different cathode compositions under the same ALD deposition conditions. All the coated cathodes were found to exhibit an improved electrochemical performance during long-term cycling under moderate cycling conditions. The improvement in the electrochemical performance after Al2 O3 coating is attributed to the suppression of parasitic side reactions between the electrode and the electrolyte during cycling. Furthermore, conductive atomic force microscopy (C-AFM) was performed on the electrode surface as a non-destructive technique to determine the difference in surface morphology and conductivity between uncoated and coated electrodes before and after cycling. C-AFM measurements on pristine cathodes before cycling allow clear separation between the conductive carbon additives and the embedded NCM secondary particles, which show an electrically insulating behavior. More importantly, the measurements reveal that the ALD-derived Al2 O3 coating with an optimized thickness is thin enough to retain the original conduction properties of the coated electrodes, while thicker coating layers are insulating resulting in a worse cycling performance. After cycling, the surface conductivity of the coated electrodes is maintained, while in the case of uncoated electrodes the surface conductivity is completely suppressed confirming the formation of an insulating cathode electrolyte interface due to the parasitic side reactions. The results not only show the possibilities of C-AFM as a non-destructive evaluation of the surface properties, but also reveal that an optimized coating, which preserves the conductive properties of the electrode surface, is a crucial factor for stabilising the long-term battery performance.